A survey on TCP-friendly congestion control. - Widmer, J.
New trends in communication, in particular the deployment of multicast and real-time audio/video streaming applications, are likely to increase the percentage of non-TCP traffic in the Internet. These applications rarely perform congestion control in a TCP-friendly manner; they do not share the available bandwidth fairly with applications built on TCP, such as Web browsers, FTP, or e-mail clients. The Internet community strongly fears that the current evolution could lead to congestion collapse and starvation of TCP traffic. For this reason, TCP-friendly protocols are being developed that behave fairly with respect to coexistent TCP flows. We present a survey of current approaches to TCP friendliness and discuss their characteristics. Both unicast and multicast congestion control protocols are examined, and an evaluation of the different approaches is presented
Keywords: FTP; Internet; TCP traffic starvation; TCP-friendly congestion control; TCP-friendly protocols; Web browsers; Bandwidth sharing; Congestion collapse; E-mail clients; Multicast communication; Multicast congestion control protocols; NonTCP traffic; Real-time audio/video streaming; Unicast congestion control protocols